2014
DOI: 10.1088/0031-8949/2014/t159/014045
|View full text |Cite
|
Sign up to set email alerts
|

Influence of MeV helium implantation on deuterium retention in self-ion implanted tungsten

Abstract: The influence of helium implanted with MeV energy on deuterium retention in damaged tungsten was investigated. Damage was introduced into the material using self-ion implantation. Two different cases -low (0.02 dpa) and high (0.89 dpa) W damage levels were investigated. Helium was introduced into the resulting damage zone using MeV ion

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
2
7
0
Order By: Relevance
“…Therefore, He atoms can stay in W up to very high temperatures. Helium trapped in single vacancies, vacancy clusters, and bubbles desorbs in the range of 1500-2000 K [14] or even at higher temperatures in the case of the high damage produced by MeV ions [15,16]. Therefore, one could expect a high He concentration in the surface layer under intensive plasma irradiation.…”
mentioning
confidence: 99%
“…Therefore, He atoms can stay in W up to very high temperatures. Helium trapped in single vacancies, vacancy clusters, and bubbles desorbs in the range of 1500-2000 K [14] or even at higher temperatures in the case of the high damage produced by MeV ions [15,16]. Therefore, one could expect a high He concentration in the surface layer under intensive plasma irradiation.…”
mentioning
confidence: 99%
“…We investigate how various He concen-trations affect D retention. In a previous study it was shown that 1000 appm as implanted He at 300 K does not affect D retention in self-damaged W [25]. In the experiment presented herein, this finding will be tested for He concentrations larger by one order of magnitude.…”
Section: Introductionmentioning
confidence: 80%
“…Little is known about D retention in He implanted and annealed tungsten. It was shown in literature that when one anneals a He containing W sample no He is released after thermal treatment up to 2000 K [25,30]. This is explained by the high detrapping energy that is necessary to release He from a vacancy or vacancy cluster to which it gets bound during the implantation [9,49].…”
Section: Retention In 1700 K Annealed He Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Charged particles accelerated to high energies present an efficient means for the production of displacement damage for a reasonable experimental time period at the levels being of interest for fusion research. This method is widely used in fusionoriented investigations [7][8][9][10][11][12][13][14]. The method has been also taken in our research and it was developed on the basis of experimental facilities at NRC "Kurchatov Institute".…”
Section: Introductionmentioning
confidence: 99%